Improving Cardiorespiratory Ability in Productive Age Smokers with Bodyweight Interval Training in Surabaya City - Rinarto, Nisha Dharmayanti; Mayasari, Ayu Citra; Susanti, Ari (State Islamic University of Sunan Ampel, 2025)
Cardiorespiratory ability was influenced by many factors, including smoking habits and physical exercise. In active and passive smokers, cigarette concentrate could cause various lung and heart diseases. Both were important organs related to cardiorespiratory ability. The purpose of this study was to examine the effectiveness of bodyweight interval training in improving cardiorespiratory ability. This study used an experimental research design, specifically a true experimental design with a pre-post control group approach. The study was conducted in the Surabaya area, particularly at SMA Labschool UNESA Lidah Wetan. The population of this study consisted of adolescent smokers in Surabaya aged 15–17 years, totaling approximately 13.83 million people. The sampling technique used was simple random sampling, and 100 respondents were selected and divided into a control group and a treatment group. Based on the analysis results, the study concluded that there were differences before and after bodyweight interval training in both the control and treatment groups, as indicated by a significance value of p < 0.05. Based on these findings, it was suggested to adopt a healthy lifestyle by quitting smoking, as smoking harmed health. Regular and consistent exercise, especially bodyweight interval training, could improve physical fitness, particularly cardiorespiratory endurance, especially among smokers.